Análise de eficiência de pequenos meios de hospedagem da Estrada Real - Nazareth, Luiz Gustavo Camarano (2009)
This study was carried out aiming to identify the economical-financial efficiency of small hosting establishments (SHE) along the Estrada Real (the Royal Road) through the Data Envelopment Analysis ( DEA) methodology , so as to investigate the existence of homogeneity in the management efficiency in such establishments, build comparative efficacy levels (productive, technical and scale); analyze the enterprises´ risk and reward and, finally, map up new efficiency patterns for the SHE´s taken as "inefficient" in the São João del-Rei and Tiradentes region. For that purpose a quantitative analysis was carried out, with exploratory aims, of segment´s historical information, bookkeeping and account statements of the small tourism-related enterprises, over the year of 2008. The sample evidenced that productive efficacy is barely homogeneous. Once the differences inherent to the nature of each one of the decision-making units became known, the rising of large efficiency discrepancies was expected. Nevertheless, that was not verified. In the analysis of the SHE´s technical efficiency, the financial management question proved to be quite homogeneous, as 50% of the analyzed endeavors were classified as 100% efficient, management-wise. However the scale inefficiency was verified through 83.66% of the sample. Several decision-making units (DMU) taken as inefficient offered high risk to the entrepreneurs while several efficient DMU´s offered high rewards and low risk. The DEA, allied to the analysis of risk and reward contributes to a better adaptation of a economical-financial management of the "inefficient" enterprises and, consequently, to the increase in competitiveness of the intangible product ER (RR). This is not a revolutionary study: the call for analysis rises from a research-thirsty segment in which the universe of possibilities remains unknown.